The Analysis of Illocutionary Acts Used in The Speech Video by Nouman Ali Khan “Ramadan: The Month of Hope” - Chairunissa, Nabila Zahwa (Jurnal Penelitian Mahasiswa Indonesia, 2023)
This study focuses on Nouman Ali Khan's speech entitled “Ramadan: The Month of Hope '' with used of illocutionary approaches. The objective of this study is to explain and describe the various types of Illocutionary acts and their related functions. The research for this topic was conducted using a descriptive qualitative research. The data were collected using observation checklists then they were classified into some types of speech acts based on Yule’s theory. The results of this study show that there were four types of illocutionary acts; representative with cover five functions: Stating, informing, describing, clarifying & concluding. And followed by expressive with cover three functions: praising, hope & apologies and directives with cover four functions: advising, asking, telling, praying and the last one commissive with cover one function: guaranteeing. Additionally, (1) The representatives were the most frequent types of illocutionary act appeared in the speeches which have total 144 utterances (81,36%) with function: stating, informing, describing, clarifying & concluding. (2) The second highest type is expressive that have a total 17 utterances (9,61%) with functions: praising, hope & apologies. (3) The third, directives who have 15 total of utterances (8,47%) with function: advising, asking, telling, praying (5) The last one is commissive with 1 utterance (0,56%) with function: guaranteeing.